2013
DOI: 10.1038/cddis.2013.479
|View full text |Cite
|
Sign up to set email alerts
|

Keratan sulfate expression in microglia is diminished in the spinal cord in experimental autoimmune neuritis

Abstract: Experimental autoimmune neuritis (EAN) is an animal model of Guillain–Barré syndrome, an inflammatory demyelination disease of the peripheral nervous system. Although this disease has been extensively studied on peripheral nerves, the pathology of the central nervous system has not been fully understood. Previous studies demonstrate that expression of keratan sulfate (KS), the sugar chain of proteoglycan, is associated with activated microglia/macrophages accumulated after neuronal injuries. Unexpectedly, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Matsui et al (25) reported that IL-1β, TNF-α and IFN-γ were increased in the spinal cord of EAN rats, whereas anti-inflammatory cytokines, including IL-4 and IL-10, were decreased (25). Serum IFN-γ was also elevated in patients with GBS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Matsui et al (25) reported that IL-1β, TNF-α and IFN-γ were increased in the spinal cord of EAN rats, whereas anti-inflammatory cytokines, including IL-4 and IL-10, were decreased (25). Serum IFN-γ was also elevated in patients with GBS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, KS also actively participates in the development of neural system [5,6]. Much more recently, KS was evidenced to be involved in the microbial infection process of corneal stroma and the progress of experimental autoimmune neuritis [1,7]. Taken together, KS plays a biologically important role in various physiological processes, and, as a promising drug candidate, it has been developed as an active ingredient in different pharmaceutical formulations [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Matsui and co-authors, the investigators have shown for the first time a negative correlation between the expression of KS by microglia and the progress of the experimental auto-immune neuritis (EAN) [14]. In this pathology, a demyelination process characterizes the auto-immunological response on cells of the peripheral nervous system.…”
Section: Inflammationmentioning
confidence: 99%
“…In this pathology, a demyelination process characterizes the auto-immunological response on cells of the peripheral nervous system. Matsui and coworkers had the goal of studying the role of KS in this immunological process [14]. They noticed that KS expression is fairly diminished in cases of EAN rat models.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation